Pengaruh Electronic Word Of Mouth, Brand Image dan Promotion Terhadap Keputusan Pembelian di Hotel Santika BSD City - Siti Nurjanah; Surono (Human Capital Development, 2023)
This study aims to determine and investigate the effect of electronic word of mouth, brand image, and promotions on purchasing at Hotel Santika BSD. The sample of this research was 153 respondents who were customers of Hotel Santika BSD, where the respondents were determined using purposive sampling. The research method used was a quantitative research method. The analytical method uses SmartPLS. The results showed that electronic word of mouth, brand image, and promotion had a positive effect on purchasing decisions.